Analisis Perbandingan Biaya Pengelolaan Limbah Medis Padat Antara Sistem Swakelola dengan Sistem Outsourcing di Rumah Sakit Kanker “Dharmais” - Purwohandoyo, Ari (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
Based on the principle of "the polluter pays", every health care need to be financially responsible for the management of their waste safely. Such costs should be funded by a special allocation of hospital budgets. Total expenses generally consist of an initial capital investment, depreciation of equipment and buildings, the cost of operation of these elements such as personnel and consumables, vehicle operating costs, third-party management fees, license fees, and other expenses that everything must be carefully fastidiously if it will choose the lowest cost option.This study discusses The comparative cost analyse of solid medical waste management in the "Dharmais" Cancer Hospital between self-managed system with outsourcing system. This research is a quantitative and descriptive study was done by observation, document review, and the calculation of the cost of using Activity Based Costing (ABC). The survey results revealed that the flow of medical waste management process has been running good and solid medical waste management outsourcing system is cheaper than self-managed. To reduce solid medical waste, they can do waste minimization efforts.